Participation of citizens in the drafting of the constitution and constitutional amendments in foreign countries: new approaches - Maslovskaya, Tatiana S. (Journal of the Belarusian State University. Law, 2023)
The article discusses new approaches to the participation of citizens in the development of the constitution and amendments to it. The forms of citizen participation that are implemented simultaneously with the preparation of the project, or before such preparation, are subjected to analysis. Attention is drawn to the use of information technologies in this process. The analysis is carried out on the basis of the experience of individual foreign states, primarily the states of Western Europe (France, Luxembourg, Ireland, Iceland).